Buyuk allomalarimiz asarlarida oilada bola tarbiyasining ahamiyati haqida qarashlari. - Sodiqova, Dilfuza (Журнал Педагогики и психологии в современном образовании, 2021)
attitudes towards the child lead to different behavior, the appearance of good forms of behavior not only affects the child’s psyche, but also contributes to his physiological growth, and bad behavior leads to various disorders of the client, but also to changes in the child’s body, it was also argued that changes in behavior lead to physical and mental health as a result of moderation of the child’s behavior